Current trends of professional competence formation of students of higher education institutions of PRC - Zhang, Wei (Educological discourse, 2023)
The article examines the issue of modern trends in the formation of professional competence of students of higher education institutions. The definition of the concept of professional competence is analyzed based on various definitions and the own vision of this concept is formulated as: a set of knowledge, skills, abilities and qualities that are necessary for the successful performance of a certain professional activity. It was determined that the most significant trends in the formation of professional competence in the educational space of higher education institutions include: active use of information and digital technologies; practice-oriented educational programs; interdisciplinarity and flexibility; development of soft skills; participation in research activities. It is noted that modern trends in the formation of professional competence are also associated with active interaction between educational institutions and employers. This approach makes it possible to take into account the needs of the labor market and train specialists who meet modern requirements. The leading experience of the higher education system of the People’s Republic of China in the formation of the professional competence of students was studied. The main trends of the above-mentioned issue in the education system of the People’s Republic of China include: Internet education programs; use of modern technologies in education; interactive learning methods; internship programs; in-depth study of foreign languages; international mobility; development of soft skills. It was established that the formation of students’ professional competence is a complex and multifaceted process that requires a comprehensive approach and constant improvement of existing methods and approaches.